Woody leguminous trees: New uses for sustainable development of drylands. (17th November 2017) - Castro, David; Urzúa, Johanna; Rodriguez-Malebran, Mariano; Inostroza-Blancheteau, Claudio; Ibáñez, Cristian
ABSTRACT: Woody leguminous species are valuable crops because of their nutritional, economic, and ecological characteristics. Such crops have aided in the recovery of marginal lands for agricultural development due to their ability to fix nitrogen, control erosion, and act as a refuge for other species, in addition to their capacity to improve soil mineral composition and microbial biodiversity. Nevertheless, some leguminous trees are recognized to be one of the worst invasive species that affect negatively biodiversity and the entire ecosystem balance. In this study, we review new global uses for some woody leguminous crops, highlighting new nutraceutical and pharmacological properties, their uses as bioenergy sources, and their ecological uses for bioremediation opening new possibilities of management. We aim to bring knowledge on the multiple benefits that these woody plants continue to provide to humans from economic, social, and environmental standpoints.